Microhabitat and morphometric variation of two chaetophoracean (chaetophorales, chlorophyta) species in tropical streams of southeastern Brazil - Branco, Ciro Cesar Zanini; Necchi Jr., Orlando [UNESP] (Wiley, 1998)
Two populations of Chaetophora elegans (Roth) C. Agardh and two of Stigeoclonium helveticum Vischer were investigated for microhabitat characteristics and morphological variation in streams of Sao Paulo State, southeastern Brazil. Different patterns of microhabitat distribution were found between species investigated. Populations of C. elegans were distributed under relatively narrow microhabitat conditions (high irradiance, low depth, moderate to high current velocity, rocky substrata and lower values of niche width) and showing little morphometric variation (colony diameter, main axis cell size, and apical branch number). Stigeoclonium helveticum occurred under more diverse microhabitat conditions, revealed by lack of significant difference between sampling units with and without the alga and wider niche width, but also exhibited relatively narrow morphometric variation (plant length, main axis cell and lateral branch cell sizes). The narrow microhabitat conditions and smaller niche width of C. elegans can explain its low abundance (percentage cover) in streams from the area studied as well as in other regions of Sao Paulo State. In contrast, the wider variation of microhabitat conditions and the higher niche widths of S. helveticum suggest that this green alga is able to grow in a high number of stream ecosystems in the region investigated, ranging from undisturbed to highly disturbed habitats. Thus, the results suggest that S. helveticum is a generalist species.
Keywords: Chaetophora; Chaetophoraceae; Microhabitat; Morphometric variation; Stigeoclonium; Stream; Chaetophora elegans; Stigeoclonium helveticum